The human ubiquitin C promoter directs high ubiquitous expression of transgenes in mice - Schorpp-Kistner, Marina; Jäger, Richard; Schellander, Karl; Schenkel, Johannes; Wagner, Erwin F.; Weiher, Hans; Angel, Peter (Nucleic acids research, 1996)
Transgenic mice provide one of the best experimental systems to study gene function in vivo. Although transgenic mice carry the additional genetic material in e